The Jesuits' Estate Question, 1760-1888 : A Study of the Background for the Agitation of 1889 - Dalton, Roy, C. (Book collections on Project MUSE., 1968)
More than a hundred years of trouble followed the land grant of half a million acres along the St. Lawrence River to the Jesuits. Professor Dalton provides a badly needed investigation into this area of Canadian history.